CCUS policy research for carbon neutrality - YAO Xing; WEN Xin; WU Jiahao; ZHU Lei*; LIU Yu; HUANG Yan; SUN Shuxin (能源环境保护)
The introduction of China′s "Dual Carbon" strategic goals has positioned Carbon Capture, Utilization, and Storage (CCUS) technology as the sole option for realizing the low-carbon utilization of fossil energy and as a crucial means to support the carbon neutrality objective. However, during the critical period transitioning from the industrial demonstration to the commercial application phase, a disconnect exists between technology innovation, project operation, market development, and policy formulation. The disconnect limits the large-scale deployment and industrial development of CCUS technology. Therefore, it is vital to establish a policy system that includes both a normative support system and various policy tools for CCUS development. This paper reviews the latest achievements in policy mechanism research in the field of CCUS, considering the new situation faced by carbon peaking and carbon neutrality. It discusses the different types of policy tools adopted by major countries and regions, such as the United States, the United Kingdom, Australia, and the European Union, to promote CCUS development. Additionally, it analyzes the synergistic effects between macro-support policies, administrative order policies, financial incentive policies, and market mechanism policies. Finally, taking into account the opportunities and challenges faced by the development of CCUS, this paper proposes suggestions for designing incentive policies to facilitate the industrial development of China′s CCUS industry. The research results of this paper provide valuable insights and references for policymakers and researchers dealing with climate change and the "Dual Carbon" goals.